Evolutionary game dynamics of combining the payoff-driven and conformity-driven update rules. (November 2020) - Lin, Jingyan; Huang, Changwei; Dai, Qionglin; Yang, Junzhong
Abstract: Conformity has been found to play a significant role in promoting cooperation. In this paper, we propose a spatial prisoner's dilemma game with a novel strategy updating rule, combining the payoff-driven and conformity-driven update rules. For the noise strengths κ 1 = κ 2 = 0.1, our results reveal that the dynamics of this model is always absorbed into the frozen state. Three phases are appeared in the order of full cooperators, bistability and full defectors with increasing temptation to defect b . In the bistability phase, the dynamics can evolve into either a full-cooperator state or full-defector state, and the final steady states of the model are mainly determined by the synchronous expanding along the smooth boundaries of the cooperator clusters. Moreover, the full κ − b phase diagram is illustrated to explore the effects of noise on the evolution of cooperation in the proposed model, and the bell-shape phase diagrams indicate that there exists an optimal uncertainty for the emergence and maintenance of cooperation. Furthermore, the effects of distinct κ 1 and κ 2 on the evolution of cooperation have also been investigated. Interestingly, the coexistence of cooperators and defectors could be found in appropriate parameter regions. In addition, we also consider another way to integrate the payoff-driven and conformity-driven strategy updating rules, and the outcomes clearly show that the evolution of cooperation can be significantly enhanced within an optimal region of conformity strength. These observations enrich our knowledge of the evolution of cooperation in the games when the payoff-driven and conformity-driven update rules are combined.